2020
DOI: 10.3390/buildings10030038
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Evaluation of Cement-Based Building Materials Modified Using Marble Powder Sourced from Industrial Wastes

Abstract: This paper presents an experimental study on the assessment of the cement-based materials properties made with marble powder (MP) at different replacement ratios (0%, 5%, 10%, and 15%) of cement by using the ultrasonic pulse velocity (UPV) test. The used MP has a Blaine fineness similar to that of Portland cement. The physical and the chemical characteristics of Portland cement and MP were determined. To determine the UPV values, cubic specimens (50 × 50 × 50 mm3) of cement paste and mortar were prepared and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…It is known that bleeding depends on the cement type, 18 admixtures, 20,21 w/c ratio, 20,22 aggregate size and type, 23 and the scale of the used cementitious mixes (i.e., concrete, mortar, or paste) 17,24 . Concrete subjected to uncontrolled bleeding may need expensive repair, or even replacement of the entire concrete element 25,26 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that bleeding depends on the cement type, 18 admixtures, 20,21 w/c ratio, 20,22 aggregate size and type, 23 and the scale of the used cementitious mixes (i.e., concrete, mortar, or paste) 17,24 . Concrete subjected to uncontrolled bleeding may need expensive repair, or even replacement of the entire concrete element 25,26 …”
Section: Introductionmentioning
confidence: 99%
“…17,24 Concrete subjected to uncontrolled bleeding may need expensive repair, or even replacement of the entire concrete element. 25,26 The significant impact of the bleeding process on the durability of concrete requires the control of this process. To control the bleeding process, the following question is crucial: How do the physical properties of binder grains influence the bleeding process of concrete, and consequently its mechanical properties and durability?…”
Section: Introductionmentioning
confidence: 99%
“…The use of wastes for partial replacement of cement, such as ground granulated blast furnace slag, fly ash, marble powder and glass powder have been studied by many researchers [ 13 , 14 , 15 ]. However, glass can be considered as the most appropriate as cement substation, due to its chemical composition and physical properties [ 16 , 17 , 18 , 19 , 20 ] as well as its abundance in the landfills in large quantities.…”
Section: Introductionmentioning
confidence: 99%
“…UPV has been widely used in evaluating different concrete conditions. Recently, there have been studies that used UPV to evaluate building materials modified using industrial wastes [ 9 , 10 ]. In the study of Sadowski et al [ 9 ], the results confirmed the potential of using the hybrid ultrasonic-neural method in analyzing the compressive strength of concrete screeds with materials from industrial waste.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Sadowski et al [ 9 ], the results confirmed the potential of using the hybrid ultrasonic-neural method in analyzing the compressive strength of concrete screeds with materials from industrial waste. Another study by Seghir et al [ 10 ] used UPV in evaluating cement-based building materials with marble powder. The results of the research showed that incorporation of marble powder affect the UPV, apparent density, and compressive strength.…”
Section: Introductionmentioning
confidence: 99%